2016
DOI: 10.1071/fp15216
|View full text |Cite
|
Sign up to set email alerts
|

Root biomass in the upper layer of the soil profile is related to the stomatal response of wheat as the soil dries

Abstract: Terminal drought is a common abiotic stress affecting wheat yield in Mediterranean-type environments. As terminal drought develops, top layers of the soil profile dry, exposing the upper part of the root system to soil water deficit while deeper roots can still access soil water. Since open stomata rapidly exhausts available soil water, reducing stomatal conductance to prolong availability of soil water during grain filling may improve wheat yields in water-limited environments. It was hypothesised that genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 53 publications
4
27
0
Order By: Relevance
“…), but is known to close its stomata in response to soil drying while leaf water potential also declines (Saradadevi et al. , ), so carbon assimilation and hence, growth would be reduced, supporting the observation in this study. ‘Janz’ is a widely adapted cultivar, which may be related to its conservative behaviour as observed here in terms of shoot biomass under WW conditions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…), but is known to close its stomata in response to soil drying while leaf water potential also declines (Saradadevi et al. , ), so carbon assimilation and hence, growth would be reduced, supporting the observation in this study. ‘Janz’ is a widely adapted cultivar, which may be related to its conservative behaviour as observed here in terms of shoot biomass under WW conditions.…”
Section: Discussionsupporting
confidence: 85%
“…All of the cultivars in this study, except 'Kukri', are considered drought tolerant (see references in Table 1) and were bred in different environments. For example, 'Drysdale' was developed for high transpiration efficiency through selection based on carbon isotope discrimination (Condon et al 2004), but is known to close its stomata in response to soil drying while leaf water potential also declines (Saradadevi et al 2014(Saradadevi et al , 2015, so carbon assimilation and hence, growth would be reduced, supporting the observation in this study. 'Janz' is a widely adapted cultivar, which may be related to its conservative behaviour as observed here in terms of shoot biomass under WW conditions.…”
Section: Discussionsupporting
confidence: 75%
“…The SEM provided evidence that the topsoil roots were critical factor influencing yield components (spike number, number of grains, thousand kernel weight), especially when crops did not suffer drought stress; however, excessive roots in the topsoil pose a risk to grain yield through strong competition for soil water during vegetative growth, leading to insufficient soil water after anthesis. In addition, more roots in the dry topsoil layers would increase abscisic acid (ABA) levels, which would decrease stomatal conductance and photosynthesis (Du et al, 2013; Saradadevi et al, 2016; Saradadevi et al, 2014), possibly influencing grain filling and reducing grain yield.…”
Section: Resultsmentioning
confidence: 99%
“…For example, bulk leaf tissue ABA of water‐stressed plants was at least 50% greater than xylem sap ABA. It has been suggested that xylem sap ABA has better control of stomatal conductance than bulk leaf tissue ABA (Saradadevi, Bramley, Palta, Edwards, & Siddique, 2016) because it is thought that the effect of ABA on stomatal conductance is driven by the accumulation of apoplastic ABA (Sirichandra, Wasilewska, Vlad, Valon, & Leung, 2009). However, we observed greater concentrations of ABA, ABA‐GE, and phaseic acid in bulk leaf tissue than in xylem sap.…”
Section: Discussionmentioning
confidence: 99%